2012
DOI: 10.1521/aeap.2012.24.6.564
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Serosorting and Intention to Serosort Among Men Who Have Sex with Men, San Francisco

Abstract: The objectives of this study were to characterize men who have sex with men (MSM) with intention to serosort and to identify factors associated with subsequent failure, defined as potentially discordant unprotected anal intercourse (PDUAI) events. Time-location sampling was used to recruit MSM into a longitudinal study of seroadaptive behaviors in San Francisco. Intention to serosort was assessed at baseline, while sexual behavior in the subsequent 6 months was assessed at follow-up. HIV-negative frequent meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…In the case that a transwoman participant was HIV positive and reported her partner’s HIV status as negative, and vice versa for a transwoman who was HIV-negative and reported her partner as being HIV-positive, the partnership was categorized as serodiscordant. Transwomen’s partnerships with those of an unknown HIV status were also categorized as serodiscordant, consistent with prior literature [23, 24]. We calculated assortativity by race, partner status (main, casual, or commerical), HIV serostatus, and IDU between transwomen and their sexual networks using Newman’s assortativity coefficient.…”
Section: Methodsmentioning
confidence: 95%
“…In the case that a transwoman participant was HIV positive and reported her partner’s HIV status as negative, and vice versa for a transwoman who was HIV-negative and reported her partner as being HIV-positive, the partnership was categorized as serodiscordant. Transwomen’s partnerships with those of an unknown HIV status were also categorized as serodiscordant, consistent with prior literature [23, 24]. We calculated assortativity by race, partner status (main, casual, or commerical), HIV serostatus, and IDU between transwomen and their sexual networks using Newman’s assortativity coefficient.…”
Section: Methodsmentioning
confidence: 95%
“…Behavioral surveys among MSM usually estimate the association between alcohol use and risky sex without considering the effect of sensation seeking, 1 which is a potential confounder in this causal pathway. 4 Using the findings of this study, investigators can consider the confounding effect of sensation seeking and estimate the adjusted effect of alcohol use on risky sex among MSM.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Previous research showed that this risk was higher in heavy alcohol drinkers than in low-level alcohol drinkers or non-drinkers in both HIV-positive and HIV-negative MSM. 1 …”
Section: Introductionmentioning
confidence: 99%
“…For analytical purposes, we combined into one item labeled “withdrawal” persons who used withdrawal as either insertive or receptive partner. These eight items are commonly used HIV risk reduction practices (Chen et al, 2012; Parsons et al, 2005; World Health Organization, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Substance-use strategies include not sharing drug paraphernalia, or rinsing shared syringes and rigs in a bleach–water solution (Abdala, Crowe, Tostov, & Heimer, 2004; Abdala, Gleghorn, Carney, & Heimer, 2001; Cox, Lawless, Cassin, & Geoghegan, 2000; Koester, Glanz, & Baron, 2005; Richard, Mosier, & Atkinson, 2002). Sexual strategies include considering HIV status (serosorting) when deciding whether to share drug paraphernalia or to engage in condomless anal intercourse (CAS; Chen, Vallabhaneni, Raymond, & McFarland, 2012; Eaton, Kalichman, O’Connell, & Karchner, 2009; Philip, Yu, Donnell, Vittinghoff, & Buchbinder, 2010; Yang, Tobin, & Latkin, 2011; Zablotska et al, 2009), or using sexual positioning or withdrawal during CAS (Binson, Pollack, Blair, & Woods, 2010; Dubois-Arber, Jeannin, Lociciro, & Balthasar, 2012; Marks et al, 2010; McDaid & Hart, 2012; Parsons et al, 2005; Van de Ven et al, 2002). Biomedical strategies (i.e., pre- and post-exposure prophylaxis, and undetectable viral loads) to reduce HIV risk (Campbell, Herbst, Koppenhaver, & Smith, 2013) are not yet widely used among HIV–negative MSM (Krakower et al, 2012; Mutua et al, 2012), but their acceptability is increasing (Escudero et al, 2014; Holt, 2014; Young, Li, & McDaid, 2013; Young & McDaid, 2014).…”
Section: Introductionmentioning
confidence: 99%